Sero-epidemiology of infectious bovine rhinotracheitis and brucellosis in organised dairy farms in southern India - KRISHNAMOORTHY, P; PATIL, S S; SHOME, RAJESWARI; RAHMAN, H (The Indian Journal of Animal Sciences, 2015)
The present study was conducted to know the seroprevalence of infectious bovine rhinotracheitis (IBR) and burcellosis and its epidemiology in organised dairy farms in southern India. Sera samples (559) 398 cattle and 161 buffaloes) were collected from 6 organised dairy farms in southern India. Samples were screened for IBR by avidin biotin ELISA and brucellosis by RBPT and indirect ELISA. The overall apparent prevalence were 61.54%, 10.20% and 11.63% for IBR, Brucella by RBPT and iELISA respectively. The state-wise seroprevalence showed highest in Andhra Pradesh for IBR and Karnataka for both IBR and brucellosis; lowest in Tamil Nadu for both the diseases. There was no significant difference in male and female in seroprevalence of these diseases. Crossbred cattle showed high seroprevalence for IBR and Brucella antibodies when compared to indigenous cattle breeds. Buffaloes showed increased seroprevalence for IBR and Brucella when compared to cattle. The IBR seropositive animals showed positive relationship with increase in age. Animals with history of abortions showed seroprevalence of 100% for IBR and 40-50% for brucellosis. The animals with history of reproductive problems showed increased seroprevalence when compared to apparently healthy bovines. The seropositivity for both IBR and brucellosis were 2.76% and 29.19% in cattle and buffaloes, respectively and with overall seropositivity of 10.38%. Thus IBR and brucellosis seroprevalence has increased over the years and there is a need to tackle these diseases effectively by zoosanitary measures and control programmes in organised dairy farms which would benefit the dairying in Southern India.